2021
DOI: 10.1177/0959683620988031
|View full text |Cite
|
Sign up to set email alerts
|

Carbon accumulation in peatlands along a boreal to subarctic transect in eastern Canada

Abstract: In this study, we investigated the links between peat carbon accumulation and past ecological and hydrological conditions in three peatlands (Bouleau, Mista, Auassat) which developed along a South-North transect within a watershed encompassing the boreal and subarctic domain in Eastern Canada. Peatland development and long-term apparent rates of carbon accumulation (LORCA) were asynchronous in the watershed, suggesting an influence of both latitude and topography (altitude) on the length of the growing season … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 67 publications
5
26
3
Order By: Relevance
“…During the Little Ice Age, permafrost aggradation was documented in ombrotrophic peatlands of the boreal and subarctic regions of northwestern Québec (Thibault and Payette, 2009; Tremblay et al, 2014). During this cold climatic episode, northern peatlands in eastern Canada registered important lowering in CAR (Garneau et al, 2014; Magnan and Garneau, 2014; Primeau and Garneau, 2021; van Bellen et al, 2013) as also observed in the current study sites without evidence of relic permafrost nowadays. We can hypothesize that persistence of ice lenses within the horizons with very short growing seasons may have limited peat accumulation for several decades.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…During the Little Ice Age, permafrost aggradation was documented in ombrotrophic peatlands of the boreal and subarctic regions of northwestern Québec (Thibault and Payette, 2009; Tremblay et al, 2014). During this cold climatic episode, northern peatlands in eastern Canada registered important lowering in CAR (Garneau et al, 2014; Magnan and Garneau, 2014; Primeau and Garneau, 2021; van Bellen et al, 2013) as also observed in the current study sites without evidence of relic permafrost nowadays. We can hypothesize that persistence of ice lenses within the horizons with very short growing seasons may have limited peat accumulation for several decades.…”
Section: Discussionsupporting
confidence: 82%
“…Although the recent Sphagnum expansion was not supported by detailed 210 Pb chronologies in the lateral cores, the data suggest a widespread ecosystem state shift in both peatlands corresponding to the beginning of the 20th century. Similar recent Sphagnum expansion was also documented in other northern peatlands (Loisel and Yu, 2013; Primeau and Garneau, 2021; van Bellen et al, 2013, 2018b). When considering the current climate warming trend, this ecosystem change coincided with the registered increase in temperature and growing degree-days (>0°C) from 1950 to 2017 (Supplemental Figure S1, available online).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Moreover, the apparent drying trend could simply reflect an enhanced vertical Sphagnum moss growth, promoted by increasing growing degree days in the last decades (Fig. 5b; Magnan et al 2018;van Bellen et al 2018;Primeau and Garneau 2021;Robitaille et al 2021). The rapid accumulation of organic matter may have exceeded the capacity of adventitious roots to develop higher in the soil profile, compromising the access to oxygen.…”
Section: Synchronous Changes In Iwue Over Timementioning
confidence: 99%